2013
DOI: 10.1093/bjsw/bct007
|View full text |Cite
|
Sign up to set email alerts
|

Making Threshold Decisions in Child Protection: A Conceptual Analysis

Abstract: His previous posts include working as a lecturer at Northumbria University, and as a social worker and front line manager in both the statutory and voluntary sectors in England. His interests are in social work education, child protection, family support, child and family assessment, and parental engagement with services. Danielle Turney is a Senior Lecturer in Social Work at the School for Policy Studies, University of Bristol. Before taking up her present post, she worked at Goldsmiths College, University of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 28 publications
0
72
0
2
Order By: Relevance
“…Dingwall, Eekelaar, and Murray (1995) in their study of child protection practice found that signs are much more likely to be labelled abuse if parents breach professionals' expectations of morally acceptable parental behaviour, being willing to appear contrite, honest, and cooperative, to be keeping their homes tidy: to appear to be doing the best under the circumstances. These expectations of parents are also heuristic devices, simplifications to aid rapid sense-making and decisions (Platt & Turney, 2014). Because signs of abuse are ambiguous, judgements are often made on perceptions of the child's wider social circumstances, and those circumstances are judged on the basis of a profession's knowledge claims.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dingwall, Eekelaar, and Murray (1995) in their study of child protection practice found that signs are much more likely to be labelled abuse if parents breach professionals' expectations of morally acceptable parental behaviour, being willing to appear contrite, honest, and cooperative, to be keeping their homes tidy: to appear to be doing the best under the circumstances. These expectations of parents are also heuristic devices, simplifications to aid rapid sense-making and decisions (Platt & Turney, 2014). Because signs of abuse are ambiguous, judgements are often made on perceptions of the child's wider social circumstances, and those circumstances are judged on the basis of a profession's knowledge claims.…”
Section: Discussionmentioning
confidence: 99%
“…Here "sense-making" refers to the complex set of processes that set real-world decision-making apart from technical-rational models. In complex uncertain situations where environmental cues may be fallible and situations are subject to competing versions of events, this "sense-making" is a vital element in forming judgements in complex and ill-defined situations where clearly defined options and unambiguous evidence are not immediately available (Platt & Turney, 2014). In complex uncertain situations where environmental cues may be fallible and situations are subject to competing versions of events, this "sense-making" is a vital element in forming judgements in complex and ill-defined situations where clearly defined options and unambiguous evidence are not immediately available (Platt & Turney, 2014).…”
mentioning
confidence: 99%
“…A failure to accept or use services identifies parents as 'unco-operative' and raises levels of concern, making compulsory measures more likely (Platt, 2006). Conversely, where parents are willing to work with children's services, higher levels of risk can be managed (Platt and Turney, 2013). Emergency protection powers are used where families in extreme crisis refuse to agree to placement of their child in foster care or with relatives, and offers of s.20 accommodation sometimes make clear that they cannot really be refused (DH 2001;Masson 2005).…”
Section: Prevention and The Children Act 1989mentioning
confidence: 99%
“…Internal variability in decision outcomes represents an ethical difficulty that is not easily resolved. Platt and Turney [28] offer a cogent critique of attempts to standardise threshold decisions on several counts: firstly, that the complex decision-making context involves numerous factors beyond the actual case characteristics or agency decision-making tool; secondly, that the worker's own sense-making processes contain numerous aspects to do with cognitive processes, intuition emotion and values; thirdly, that neither linear, rational decision-making nor the use of heuristics and biases as "defective" are realistic appraisals of real-life decision-making. They also point out that the various types of abuse and varied circumstances it occurs in make comparing them in order to make a distinct "line in the sand" impossible.…”
Section: The Ethical Consequences Of Variabilitymentioning
confidence: 99%
“…Others argue that heuristics (short-hand rules of thumb derived from practice experience) are not necessarily problematic, but the complex use of short cuts in response to recognised patterns that are often correct when used in their specific environmental contexts. It is this proposition on which proponents of ecological rationality and naturalistic decision-making essentially rely [28,132,133]. Hogarth [134] extends these ideas to consider heuristics as an aspect of the intuitive components of decision-making, which together with analytic reasoning, make up decision processes [73].…”
Section: Cognitive Processes and Group Decision-makingmentioning
confidence: 99%